Quality change on holy basil after fumigation with insecticidal essential oil formula from clove and cinnamon - Pumnuan, J.; Khurnpoon, L.; Insung, A. (My University, 2018)
The essential oil formula from clove (Syzygium aromaticum) and cinnamon (Cinnamomum bejolghota) at the ratio of 1:3 (Cl1Ci3) has been recently considered as an effective alternative fumigant against thrips (Thrips palmi) and aphid (Aphis gossypii), which are the major pests attacking exported holy basil (Ocimum sanctum) in Thailand. This study aimed to investigate the effects of the C1Ci3 formula used as fumigant on physical quality of holy basil compared to methyl bromide application. The percentage of insect mortality and change in L*, a* and b* values, as well as weight loss of holy basil, were determined. All fumigations in this study were conducted using the formula Cl1Ci3 at the concentrations of 0.0, 2.0 and 3.0 mL m-3 for 2 h with 15-min air circulation in 1 m3 fumigation chamber and compared to methyl bromide at 20 g m-3 (recommended concentration). The observations of insect mortality were conducted at 24 h after treatment. The holy basil samples were evaluated prior to the treatments, immediately after the treatments, and after 3 and 6 days at 25±1°C. The methyl bromide fumigation showed 100% mortality of all insects and its efficacy was significantly higher than that of the Cl1Ci3 formula (73.9-96.0%). Leaf burning was observed immediately after methyl bromide fumigations. On the other hand, no significant physiological changes were observed on plants fumigated with the Cl1Ci3 formula, as compared to the control.
Keywords: Aphid; Cinnamomum bejolghota; Methyl bromide; Mortality; Phytotoxicity; Syzygium aromaticum; Thrips